Andrographolide ameliorates oxidative stress, inflammation and histological outcome in complete Freund's adjuvant-induced arthritis. (1st March 2020) - Luo, Shasha; Li, He; Liu, Jingjing; Xie, Xiaoqian; Wan, Zhijie; Wang, Yale; Zhao, Zeyue; Wu, Xiaohan; Li, Xinxin; Yang, Min; Li, Xiaotian
Abstract: Objectives: As one of the main active ingredients of Chinese herbal medicine Andrographis paniculate, andrographolide is used in domestic clinical treatment for respiratory infections and inflammation. This study was designed to investigate the effects of andrographolide as an antioxidant on the level of oxidative stress, neutrophil accumulation and infiltration in joints and synovial tissue of arthritis rats induced by complete freund's adjuvant. Methods: A rat model of rheumatoid arthritis was induced by subcutaneous injection of complete Freund's adjuvant in the footpad. The model was established 14 days after induction. The treatment was performed from 14th day to 35th day with different doses of andrographolide (25, 50, 100 mg/kg) and positive control methotrexate (3 mg/kg). The effects of andrographolide on oxidative stress, neutrophil accumulation and infiltration were measured by the paw swelling, arthritis score, the hot plate test, biochemical analysis, and histology. Results: The medium and high-dose andrographolide (50, 100 mg/kg) group declined the levels of tumor necrosis factor-α, interleukin-6 and CXC chemokine ligand2, articular elastase and myeloperoxidase, and increased the levels of antioxidant enzymes superoxide dismutase, catalase, and glutathione. The activity of malondialdehyde and nitrite/nitrate in andrographolide (50, 100 mg/kg) group was weakened than the model group. The degree of swelling and arthritis score of andrographolide group was lower than the model group. The results of hot plate test showed that high dose of andrographolide significantly improved the anti-injury ability of rats; Radiological and histological results showed that the joint osteoporosis, inflammatory cell infiltration, synovial hyperplasia and other phenomena in the andrographolide group were significantly improved. Conclusions: Andrographolide acts as a protective agent for the treatment of complete freund's adjuvant induced rheumatoid arthritis by inhibiting lipid peroxidation and nitrite/nitrate levels in a dose-dependent manner, enhancing antioxidant enzyme activity, reducing levels of chemokines and inflammatory factors, preventing neutrophil accumulation and infiltration. Graphical abstract: Image 1 Highlights: Andrographolide inhibits neutrophil elastase and myeloperoxidase activity in arthritic rats. Andrographolide reduces neutrophil aggregation in joint inflammation by affecting neutrophil chemotactic factors. Andrographolide reduces arthritis oxidative stress levels, and inhibits inflammation.